Absence of Coronary Artery Disease is a Strong Negative Predictor of Major Adverse Cardiovascular Events in Patients with Chronic Kidney Disease - Tonnesen PT; Olesen KKW; Thrane PG; Gyldenkerne C; Peters CD; Buus NH; Maeng M (Clinical Epidemiology, 2023)
Pernille Tilma Tonnesen,1 Kevin Kris Warnakula Olesen,1 Pernille Gro Thrane,1 Christine Gyldenkerne,1 Christian Daugaard Peters,2,3 Niels Henrik Buus,2,3 Michael Maeng1,3 1Department of Cardiology, Aarhus University Hospital, Aarhus, Denmark; 2Department of Renal Medicine, Aarhus University Hospital, Aarhus, Denmark; 3Department of Clinical Medicine, Aarhus University Hospital, Aarhus, DenmarkCorrespondence: Michael Maeng, Department of Cardiology, Aarhus University Hospital, Palle Juul-Jensens Boulevard 99, Aarhus, 8200, Denmark, Tel +45 26703237, Email michael.maeng@clin.au.dkPurpose: To investigate the interplay between chronic kidney disease (CKD) and coronary artery disease (CAD) on the incidence of cardiovascular events in patients with suspected chronic coronary syndrome (CCS).Patients and Methods: Patients with suspected CCS who underwent first-time coronary angiography in Western Denmark between 2003 and 2016 were included in this cohort study. Moreover, an age- and sex-matched general population cohort was established. Patients were stratified according to estimated glomerular filtration rate (eGFR). Presence of CAD was defined as ≥ 1 obstructive stenosis or non-obstructive diffuse disease. Major adverse cardiovascular events (MACE) were defined as a composite of myocardial infarction, ischemic stroke, and cardiac death.Results: A total of 42,611 patients were included with a median follow-up of 7.3 years. Patients without and with CAD had MACE rates per 100 person-years that were 0.52 and 1.67 for eGFR ≥ 90 mL/min/1.73 m2, 0.68 and 2.09 for eGFR 60– 89 mL/min/1.73 m2, 1.27 and 3.85 for eGFR 30– 59 mL/min/1.73 m2, and 2.27 and 6.92 for eGFR < 30 mL/min/1.73 m2. Comparing to eGFR ≥ 90 mL/min/1.73 m2, the adjusted incidence rate ratios for MACE were 1.29 (1.10– 1.51) for eGFR 60– 89 mL/min/1.73 m2, 1.86 (1.49– 2.33) for eGFR 30– 59 mL/min/1.73 m2, and 3.57 (1.92– 6.67) for eGFR < 30 mL/min/1.73 m2 in patients without CAD, and 1.11 (1.03– 1.20), 1.71 (1.55– 1.90), and 2.46 (1.96– 3.09) in patients with CAD. The inverse relationship between kidney function and risk of MACE was confirmed when comparing patients with and without CAD to matched individuals in the general population.Conclusion: Absence of CAD is a strong negative predictor of major adverse cardiovascular events in patients with CKD.Keywords: coronary artery disease, coronary angiography, kidney function, renal insufficiency, chronic kidney disease, chronic coronary syndrome